Prehypertension in Pregnancy and Risks of Small for Gestational Age Infant and Stillbirth. Issue 3 (March 2016) - Wikström, Anna-Karin; Gunnarsdottir, Johanna; Nelander, Maria; Simic, Marija; Stephansson, Olof; Cnattingius, Sven
Abstract : It is not fully known whether maternal prehypertension is associated with increased risk of adverse fetal outcomes, and it is debated whether increases in blood pressure during pregnancy influence adverse fetal outcomes. We performed a population-based cohort study in nonhypertensive women with term (≥37 weeks) singleton births (n=157 446). Using normotensive (diastolic blood pressure [DBP] <80 mm Hg) women as reference, we calculated adjusted odds ratios with 95% confidence intervals between prehypertension (DBP 80–89 mm Hg) at 36 gestational weeks (late pregnancy) and risks of a small-for-gestational-age (SGA) birth or stillbirth. We further estimated whether an increase in DBP from early to late pregnancy affected these risks. We found that 11% of the study population had prehypertension in late pregnancy. Prehypertension was associated with increased risks of both SGA birth and stillbirth; adjusted odds ratios (95% confidence intervals) were 1.69 (1.51–1.90) and 1.70 (1.16–2.49), respectively. Risks of SGA birth in term pregnancy increased by 2.0% (95% confidence intervals 1.5–2.8) per each mm Hg rise in DBP from early to late pregnancy, whereas risk of stillbirth was not affected by rise in DBP during pregnancy. We conclude that prehypertension in late pregnancy is associated with increased risks of SGA birth and stillbirth. Risk of SGA birth was also affected by rise in DBT during pregnancy. Our findings provide new insight to the relationship between maternal blood pressure and fetal well-being and suggest that impaired maternal perfusion of the placenta contribute to SGA birth and stillbirth. Abstract : Supplemental Digital Content is available in the text.